The local environment of Cr3+ impurities in normal and x-rays irradiated carbon doped ruby: An electron paramagnetic resonance (EPR) study - Kazan, S.; Acikgoz, M.; Yalcin, O. (Elsevier, 2015)
Local environment of substitutional paramagnetic point defect (impurity) in normal and x-ray irradiated commercially available alpha-Al2O3:C samples (commercial product of Landauer, Inc.) has been studied by using the electron paramagnetic resonance (EPR) technique at room temperature. In both samples the EPR spectra showed strongly angular dependent behavior. The zero-field splitting (ZFS) parameters (ZFSPs) have been determined for substitutional Cr3+ centers. The observed additional EPR signals for x-ray irradiated sample were attributed to another center with different spin Hamiltonian (SH) parameters. In addition to the experimental findings, the ZESPs and the local structure of the Cr3+ ions were theoretically determined using superposition model (SPM) calculations. (C) 2014 Elsevier B.V. All rights reserved.
International Conference on Nanoscale Magnetism (ICNM-2013) -- SEP 02-06, 2013 -- Istanbul, TURKEY
Keywords: Irradiation; Electron paramagnetic resonance; Zero-field splitting; Cr3+